Layanan Over-The-Top (OTT) Dalam Perspektif Social Construction of Technology (SCOT) - Hutapea, Alfrida Esther Madame; Damayanti, Sari Riantika; Salsabilla, Zahwa (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Over-The-Top (OTT) services have revolutionized how individuals access and consume media content, generating new dynamics in the relationship between technology, society, and culture. This study aims to conceptually examine the development of OTT through the lens of the Social Construction of Technology (SCOT) to understand how social construction shapes the direction, meaning, and use of OTT technologies. This approach focuses on social actors, relevant groups, and the diverse interpretations of OTT, from design and adoption processes to emerging regulatory and cultural controversies. Employing a literature review method, the study draws on 15 scholarly articles from various global contexts, including Indonesia, South Korea, and Europe. The findings reveal that the adoption and perception of OTT are not solely determined by technological capabilities, but also shaped by social values, market pressures, cultural identities, and social anxieties such as Fear of Missing Out (FoMO). This study recommends a participatory approach in the development of OTT technologies to ensure greater inclusivity and responsiveness to societal needs.